Development of a Place Attachment Scale for Adolescents (PASA) and determination of its psychometric qualities - Mustafa Yüksel Erdoğdu (BMC Psychology)
Abstract Background Place attachment refers to a relationship with cognitive, emotional and behavioral dimensions that develops over time depending on the interaction of individuals with the social and physical environment. This relationship not only affects the identity development process of the individual but also determines the interaction with the social and physical environment. It is very important to determine and measure the level of this attachment and the variables affecting the level of attachment, especially during adolescence when the process of gaining identity is more intense. Within the framework of this purpose, this study aimed to develop a place attachment scale for adolescents. Method The scale data were obtained from 868 adolescents, 452 (52%) male and 416 (48%) female, living in the province of Istanbul in Turkey. The mean age of the adolescents was 17.18 years (sd = 2.13), while their mean success average was 4.18 years (sd = 3.14). Exploratory and confirmatory factor analysis and multiple group confirmatory factor analysis were conducted for test psychometric properties of the scale. Cronbach's reliability value was calculated. Results As a result of the exploratory factor analysis (EFA), it was observed that the scale consisted of three subscales: cognitive, emotional and behavioral. The parallel analysis supported this three-factor structure. The structure of the scale revealed by EFA was supported by confirmatory factor analysis (χ2 /df = 1.750, GFI = 0.92, CFI = 0.96, AGFI = 0.90, NFI = 0.92, RMSEA = 0.050), and the Cronbach’s alpha reliability values calculated for the subscales and the total scale were found to be very high. To ensure measurement invariance of the scale according to gender, multigroup confirmatory factor analysis was performed. Measurement invariance was ensured in gender groups, and it was found that the scale had a good fit. Composite reliability (CR) and average variance extracted (AVE) tests were performed to measure convergent validity, and it was found that the scale had high reliability and internal consistency. Discussion It was observed that the validity and reliability values of the scale were high.